F. Dostoevsky’s Underground Man and His Accusations to Modernity - Genys, Dainius (Literatūra, 2022)
Fyodor Dostoevsky’s literary art has served for centuries as a source of inspiration for scholars of different disciplines, opening up inexhaustible avenues of insight into human existence. The symbolic subtext of the article is an attempt to apply sociological imagination to the review of a literatural masterpiece, reconstructing and conceptualizing the author’s attitudes towards modernization. The academic intrigue stems from the question – how does modernization define a person and how does a person feel in a new society? Dostoevsky’s prominent conflict between the underground man and the social determinants that oppress him is conceptualized from sociological point of view. Through systematic and comparative analysis, the article also highlights Dostoevsky’s attitude to modernization, which is discussed in the broader context of ideas in E. Durkheim’s, Z. Bauman’s, V. Kavolis’s, Ch. Taylor’s, R. Inglehart’s, A. Giddens’s, etc. works.